STRATEGI PEMASARAN LEMBAGA PENDIDIKAN DALAM MENINGKATKAN TINGKAT KEPERCAYAAN MASYARAKAT DI SMP MUHAMMDIYAH 5 YOGYAKARTA - Sutoro, Okada Ruli (Jurnal Tawadhu, 2022)
This study aims to find out how the marketing strategy of educational institutions in increasing the level of public trust in SMP Muhammadiyah 5 Yogyakarta and how the efforts made to increase the level of public trust in SMP Muhammadiyah 5 Yogyakarta. This study uses a qualitative approach with descriptive analysis method. The data collection techniques were observation, interviews and documentation, with the respondents being vice principals, public relations and the new student admissions team (PPDB). The data analysis technique uses data reduction, and data display. While the data validity technique is through; credibility, transferability, dependability. While the data validity technique is through; credibility, transferability, dependability, and confirmability, so that the data is truly accurate and credible. The results of this study indicate that in the implementation of the marketing strategy of educational institutions in increasing the level of public trust in Muhammadiyah junior high school, this is proven by the fact that in the last period it has exceeded the target limit that public relations only provides four classes from AD class but see the enthusiasm of the parents of students into six classes, namely the AF class. Then the strategy used in marketing is a direct and indirect strategy, namely a direct strategy using brochures that are distributed at several points around the school and also through WhatsApp media. Then the indirect strategy of holding a try out event was carried out by a team from elementary schools in the vicinity of SMP Muhammadiyah 5 Yogykarta which was awarded a smartphone, and gave 2 goats to elementary schools whose students continued their studies at SMP Muhammdiyah 5 Yogyakarta